Implementation or Financing Agreement Musyarakah Against Customer in Sharia Bank Periode 2018 (Study: Bank Pembiayaan Rakyat Syariah Bangka Belitung) - Yudi Setiawan (Jurnal Ilmiah Ekonomi Islam, 2021)
Agreement is a where action one person or people bind your self against or more persons. In general people are free to make agreement not tied to particular shape can be made oral or writtrn. Financing is provision of funds or bill whinc in the equation with it. Musyarakah is a partnership agreement thet the benefits and risk will be borne together as agreed. Customers are parties who use the services of islam bank and UUS, syariah bank is a that runs is business activities based on syariah principles. Research method used in this research Empirical Juridical. The perpuse of this study is to find out how the Implementation in musyarakah financing and what are the obstcles that occur in the implementation, the implementation of the musyarakah financing agreement, implementation on the basis of syariah principles and agreement of bots parties, then in the implementation there are barriers thet the customers in this case does not perform it’s obligation in accordance eith the contents of the agreement thet has been made. In setting the matter, the ways of deliberation between the two parties do not find an agreement on the matter, then to resovle the matter is pursued by legal means throught the courts or through the arbitration body. Problem in change of islam is conducted in tree ways, nemaly though the road of peace, trough thes road the bank and with rescheduling done, then two road of arbitration, and then though the road of justice.